2008
DOI: 10.1159/000176189
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture and Moxibustion Attenuate the Progression of Renal Disease in 5/6 Nephrectomized Rats

Abstract: Background/Aim: Chronic kidney disease is a worldwide public health problem and the prevention of its progression is still a major challenge in nephrology. Specific therapies that inhibit or attenuate this process are neither available nor satisfactory. Traditional Chinese medicine has been increasingly recognized as an effective therapeutic approach in several fields of medicine. The aim of this study was to investigate the effects of electroacupuncture (EA) and moxibustion (MO) in an experimental model of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 82 publications
3
7
0
Order By: Relevance
“…Moreover, the decrease in the total cholesterol concentration in the EA treatment group (vs. the other groups) was caused by electrical stimulation at the ST36 and KI3 acupoints, which can be explained by an increase in involuntary muscle movements. These results are consistent with those of another study in which EA and moxibustion reduced blood pressure, serum creatinine, diuresis, glomerulosclerosis and tubulointerstitial kidney fibrosis in 5/6 nephrectomized rats [38]. …”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the decrease in the total cholesterol concentration in the EA treatment group (vs. the other groups) was caused by electrical stimulation at the ST36 and KI3 acupoints, which can be explained by an increase in involuntary muscle movements. These results are consistent with those of another study in which EA and moxibustion reduced blood pressure, serum creatinine, diuresis, glomerulosclerosis and tubulointerstitial kidney fibrosis in 5/6 nephrectomized rats [38]. …”
Section: Discussionsupporting
confidence: 93%
“…MO and EA have been used in TCM for centuries in the treatment of various diseases, including cardiovascular diseases and diseases involving hypertensive syndromes [7,35,36]. Recently, we demonstrated that EA-MO hindered the progression of CKD with reduced SBP/MAP and proteinuria [22]. …”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we demonstrated that EA and MO attenuate progression of renal disease by decreasing mean arterial pressure (MAP) and proteinuria [22]. To further understand these effects, we evaluated the effects of EA and MO on the metabolism of NO and on renal sympathetic nerve activity (RSNA) in a rat model of CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Systolic blood pressure (SBP) was monitored in the conscious rats using the tail cuff method (PE300; Narco Bio-Systems) at the beginning and end of the experiment [12].…”
Section: Methodsmentioning
confidence: 99%